PENGARUH STORE ATMOSPHERE, LOKASI TOKO, DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA ERAMART TIMBAU DI TENGGARONG - Ilham Ilham (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
The purpose of this study is to investigate and assess the influence Store Atmosphere, Location Stores and diversity of products on Consumer Purchase Decision Eramart and determine which variables are the most dominant influence on consumer purchasing decisions Eramart Timbau In Tenggarong.In data analysis, data analysis tools are used in accordance with the object of research to determine the amount of the Purchase Decision on Eramart is the model of multiple linear regression analysis, with a total sample of 41 people. Based on the research results presented a summary as follows: 1.) From the calculation of F test shows that together X1, X2, X3 influence on purchase decisions (Y) as shown by F test (F test) amounted to 14.570 while F table at 4.078 then (F test) = 14.570> F table = 2.838 , then the hypothesis put forward unacceptable. To determine the suitability / accuracy of variable X to variable Y obtained R = 0.522 and determination coefficient R2 = 0.272, this figure shows the relationship was of variable X to variable Y. 2.) Store Atmosphere, Location Stores and diversity of products in simultants significantly influence purchase decisions on Eramart Timbau In Tenggarong, is evidenced by (F test) amounted to 14.570 larger than F table at 2.838. From the results of correlation can be seen that the variable Store Atmosphere partially no dominant influence on purchase decisions this is evidenced by t test -0.253 <t table 1,687. It can be concluded that the second hypothesis in this study that the "Store atmosphere dominant influence on purchase decisions on Eramart Timbau In Tenggarong" rejected and not truth.Keywords: Effect of Store Atmosphere, Store Location, product diversity AndConsumer Purchase